Fusarium wilt of banana - Training manual - Blomme, Guy; Kearsley, Elizabeth; Ocimati, Walter; Dita, Miguel (2024)
This course is designed to provide a basic, to-the-point overview on Fusarium wilt of banana, its risk management and control. The course focuses on providing practical knowledge on Fusarium wilt disease management that is directly applicable in field conditions. Throughout four concise course modules, we discuss: • Module 1: What causes Fusarium wilt disease and how to recognize it. • Module 2: Risk management strategies to prevent Fusarium wilt from spreading. • Module 3: The control of Fusarium wilt using resistant cultivars. • Module 4: Farm management practices that can help to suppress the pathogen and help maintain banana production in affected areas. All the information provided is based on current scientific research on Fusarium wilt carried out by various research organizations, comprising universities, OneCGIAR and NARS, and is presented in an accessible way. We highlight disease management practices that have already provided positive results in the field with impact at scale. While management practices are often targeted to large-scale banana production systems and cultivars important for export trade, detailed attention is also given to best practices available to banana-producing small-holder farms.